Construction of oncolytic reporter influenza viral vectors and assessment of their safety following intracranial administration in rats - A. A. Pulkina; A. S. Mustafaeva; E. A. Romanovskaya-Romanko; M. A. Plotnikova; O. O. Ozhereleva; M. A. Shuklina; L. N. Kiseleva; Y. S. Alekseeva; N. S. Kurmazov; A. R. Muslimov; A.-P.S. Shurygina; M. A. Stukova (Microbiology Independent Research Journal)
INTRODUCTION: Oncolytic viruses are a promising approach for treating malignant brain tumors as part a of combination therapy. OBJECTIVE: To develop reporter influenza A viruses expressing NanoLuc luciferase and evaluate their safety following intracranial administration in rats. METHODS: Chemiluminescent reporter influenza A virus strains were obtained by reverse genetics. The NS genetic segment of the T_NS124-Luc and E_NS124-Luc strains encoded a fusion protein that combined NS1 124 and NanoLuc. In the T_NS124-2A-Luc and E_NS124-2A-Luc strains, the NS1 124 and NanoLuc sequences were separated by a 2A co-translational cleavage site. To enhance the tumor specificity of the viruses, the trypsin cleavage site (T) in the hemagglutinin (HA) protein was replaced with an elastase cleavage site (E) by introducing S342→P and R343→I substitutions in the HA region of the E_NS124-Luc and E_NS124-2A-Luc constructs. RESULTS: The obtained constructs demonstrated comparable reproductive and luminescent activity in MDCK cells. However, vectors containing the 2A site upstream of the transgene infected the glioma cell lines C6, A172, and T98G more effectively. Intracranial administration of a high dose of the virus was safe, causing no neurological or other pathological symptoms in rats. In addition, the luminescent reporter NanoLuc was expressed at the injection site without the formation of active viral progeny. CONCLUSION: This study demonstrated that a chemiluminescent influenza A virus strain can induce transgene expression at the site of intracranial injection without active viral replication.